PENERAPAN TEKNOLOGI FINANSIAL SEBAGAI INOVASI UNTUK MENINGKATKAN LITERASI KEUANGAN UMKM - Widyaningsih, Ika Utami (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2023)
This research discusses the application of financial technology as an innovation to increase the financial literacy of Micro, Small and Medium Enterprises (MSMEs) with a focus on finance in Indonesia. Innovation and financial literacy are considered crucial in supporting the development of MSMEs. The research method uses a qualitative approach with phenomenology which aims to detail and understand the subjective meaning of the experiences of Micro, Small and Medium Enterprises (MSME) owners. The research results identified three key aspects in the development of financial innovation and literacy in Indonesia, namely the growth of financial markets, increasing public understanding of finance, and advances in financial technology. Positive increases in innovation and financial literacy are expected to create significant business opportunities for MSME players, while also encouraging overall financial market growth in Indonesia. The application of financial technology is identified as a potential innovative strategy to strengthen the financial literacy of MSMEs, which in turn is expected to make a positive contribution to national economic growth